Tofacitinib and metformin reduce the dermal thickness and fibrosis in mouse model of systemic sclerosis - Karatas, Ahmet; Oz, Burak; Celik, Cigdem; Akar, Zeynel Abidin; Akkoc, Ramazan Fazil; Etem, Ebru Onalan; Koca, Suleyman Serdar (Nature Portfolio, 2022)
Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathway is important in the process of inflammation and fibrosis. The adenosine 5 '-monophosphate-activated protein kinase (AMPK) enzyme can affect JAK/STAT pathway. Tofacitinib is a pan-JAK inhibitor. Metformin activates AMPK enzyme. We aimed to investigate the therapeutic efficacy of tofacitinib and metformin on IL-17 and TGF-beta cytokines, skin fibrosis and inflammation in mouse model of systemic sclerosis (SSc). 40 Balb/c female mice were divided into 4 groups: (control, sham (BLM), tofacitinib and metformin). The mice in the tofacitinib group received oral tofacitinib (20 mg/kg/daily) and mice in the metformin group received oral metformin (50 mg/kg/day) for 28 days. At the end of 4th week, all groups of mice were decapitated and tissue samples were taken for analysis. Histopathological analysis of skin tissue was performed, and mRNA expressions of collagen 3A, IL-17 and TGF-beta were assessed by real-time PCR and ELISA. Repeated BLM injections had induced dermal fibrosis. Moreover, the tissue levels of collagen 3A, IL-17 and TGF-beta were elevated in the BLM group. Tofacitinib and metformin mitigated dermal fibrosis. They reduced dermal thickness and tissue collagen 3A, IL-17 and TGF-beta levels. Tofacitinib and metformin demonstrated anti-inflammatory and anti-fibrotic effects in the mouse model of SSc.
Keywords: Growth-Factor-Beta; Activation; Ampk; Pathogenesis; Inhibition; Pathway; Cells